2017
DOI: 10.3389/fmicb.2017.00552
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Action of Jineol Isolated from Scolopendra subspinipes mutilans against Selected Foodborne Pathogens

Abstract: This study was undertaken to assess the antibacterial potential of 3,8-dihydroxyquinoline (jineol) isolated from Scolopendra subspinipes mutilans against selected foodborne pathogens Escherichia coli O157:H7 and Staphylococcus aureus KCTC-1621. Jineol at the tested concentration (50 μL; corresponding to 250 μg/disk) exhibited significant antibacterial effects as a diameter of inhibition zones (11.6–13.6 mm), along with minimum inhibitory concentration (MIC) and minimum bactericidal concentration values found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Similarly, antimicrobial activity of the peptide lacrain, isolated from body extract of S. viridicornis showed strong bactericidal activity against Gram-negative bacteria (Chaparro and Da Silva Junior 2016). 3,8-Dihydroxyquinoline also known as jineol, isolated from S. subspinipes mutilans showed antibacterial activity by altering the release of potassium ions from food borne pathogenic strains of E. coli O157:H7 and S. aureus KCTC-1621 (Bajpai et al 2017). Several other AMPs such as Scolopendrasin I, V, VII are known to possess broad range of antimicrobial activities against drug resistant pathogens (Wenhua et al 2006; Peng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, antimicrobial activity of the peptide lacrain, isolated from body extract of S. viridicornis showed strong bactericidal activity against Gram-negative bacteria (Chaparro and Da Silva Junior 2016). 3,8-Dihydroxyquinoline also known as jineol, isolated from S. subspinipes mutilans showed antibacterial activity by altering the release of potassium ions from food borne pathogenic strains of E. coli O157:H7 and S. aureus KCTC-1621 (Bajpai et al 2017). Several other AMPs such as Scolopendrasin I, V, VII are known to possess broad range of antimicrobial activities against drug resistant pathogens (Wenhua et al 2006; Peng et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several molecules were identified containing isoquinoline group, chromene derivatives, thiazine groups, imidazoles, pyrrole-containing analogs, sulfonamides, furanones, and flavanones with known antibacterial properties (Ali et al 2016). Among other species, forest centipede, Scolopendra subspinipes , (also named as Vietnamese or Chinese Red-headed centipede) is commonly used in folk medicine, for its various health benefits in the treatment of wounds, pain, inflammation, sores and tumors (Lee et al 2017; Bajpai et al 2017; Ding et al 2016; Choi et al 2008). Mainly, distributed in East Asian countries, they are large with the maximum length of 20 cm and feeds primarily on insects, arachnids and small vertebrate animals, and encounter pathogens in their natural habitat (Bush et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers suggested that antimicrobial components of the plant extracts (terpenoid, alkaloid and phenolic compounds) interact with enzymes and proteins of the microbial cell membrane causing its disruption to disperse a flux of protons towards cell exterior which induces cell death or may inhibit enzymes necessary for amino acids biosynthesis [19,20,[28][29][30]. However, other researchers reported the inhibitory effect of these plant extracts to hydrophobicity characters of these plants extracts which enable them to react with protein of microbial cell membrane and mitochondria disturbing their structures and changing their permeability [19,20,[29][30][31][32].…”
Section: Total Antioxidant Activity (Ferric Reducing Antioxidant Powe...mentioning
confidence: 99%
“…The bactericidal activity of the purified terpenoid extracts from the selected sea weeds was carried using the agar disc diffusion method of Bajpai et al with marginal modifications [8].…”
Section: Bactericidal Assay-agar Disc Diffusion Assaymentioning
confidence: 99%